Achieving the 17 Sustainable Development Goals in a Sustainable Supply Chain 4.0 Ecosystem (2024)
Supply chains are recognized as the driving force of modern societies and economies, leading the evolution of organizational competition beyond mere product-centric operationshistorically marked by intense exploitation of natural resources and human labor- to a model of value creation which embraces sustainability as a strategic goal. This transformation is particularly following the emergence of Industry 4.0, where technological advancements are revolutionizing capabilities, processes and infrastructures, governance and management, resource utilization, and business models.